Media Pembelajaran PAI Berbasis AI: Analisis Integrasi Teori Behavioristik, Kognitivistik, dan Konstruktivistik - Fadhila Nur Azizah; Putri Anggun Bhakti Insanitaqwa; Muhammad Zaini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of Artificial Intelligence (AI) in the field of education requires integration that is not only technical in nature but also grounded in sound learning theories. This study aims to analyze the integration of behaviorist, cognitivist, and constructivist theories in the development of AI-based Islamic Religious Education (IRE) learning media, as well as to identify appropriate forms of media and their implications for improving the quality of learning. The study employs a qualitative approach using library research. Data sources include textbooks on learning psychology, articles from accredited national and international journals, as well as literature related to AI and PAI media published within the last five years. Data analysis was conducted using a descriptive-analytical approach with source triangulation. The results indicate that integrating these three theories is not sufficient by merely combining their features separately; rather, it must occur through a mechanism of mutual reinforcement within a continuous cycle: error data from adaptive exercises (behaviorist) triggers the personalization of materials (cognitivist), structural understanding becomes the subject of discussion (constructivist), and the outcomes of these discussions enrich the subsequent question bank (behaviorist). The appropriate form of media is an integrated platform that features an adaptive practice system, dynamic concept maps, and discussion forums or guided chatbots. The implications of this integration include improved conceptual understanding, long-term retention, critical thinking and collaboration skills, and the strengthening of students’ intrinsic motivation. This study recommends that educational media developers and PAI teachers adopt this integration framework when selecting and designing AI-based media.